Evaluation Of Post EIA : Water Quality Due To The Construction Of The Sungai Kinta Dam Project, Perak - Ishak, Nurfaizahwati (Universiti Sains Malaysia, 2006)
Water quality is one of the main element that is studied thoroughly in an Environmental Impact Assessment. The main scope of this case study is to determine the EIA on water quality during and after completing the construction works Sungai Kinta Dam Project, Mukim Hulu Kinta, Kinta District, Perak from 1991 until 2005. The analysis are done based on the data that were obtained from the Project Manager; Metropolitan Utilities Corporation Sdn. Bhd. The most critical issue is the turbidity because it can reflects the physical impacts to the other water quality parameters such as colour, nitrate, hardness, total suspended solids and etc. The main sources that contribute to the decreasing of water quality are the construction activities of dam and the construction of the Highway across the upper catchment areas. The water quality of Sungai Kinta that was affected will recover after both activities are completed to ensure safe and clean water can be supplied to population in Ipoh and the outlying areas. In conclusion, the water quality on the construction of the Sg. Kinta Dam Project, Perak is consistent with the evaluation of EIA that had been prepared before the project started.